The research on usability testing for users' emotion using game design - Ahmad, I.; Jaafar, Azizah; Mohd Kamil, Mohd Hafiz Faizal (2012)
Computer game design process should be developed carefully so that products produced computer games could provide a big impact on users. Studies related to computer game design and its impact on the users' emotional is getting less response. Emotions can be seen not only from changes in human behavior but can also be done through changes in facial expression. This paper illustrates the part of the brief study related to changes in facial expression showed by the users on computer game design produced. According to some researchers in the field of affective computing, attractive design can reflect the users' satisfaction and usability. By using video recording, the result of observation of the reaction of the users facial expression while they playing a game, the researchers looked at changes in facial expression at the basis for identify the kind of emotion emitted by the users.